Anomalous in-plane anisotropic Raman response of monoclinic semimetal 1 T´-MoTe 2 - Qingjun Song (Nature Portfolio, 2017)
Abstract The recently discovered two-dimensional (2D) semimetal 1 T´-MoTe2 exhibits colossal magnetoresistance and superconductivity, driving a strong research interest in the material’s quantum phenomena. Unlike the typical hexagonal structure found in many 2D materials, the 1 T´-MoTe2 lattice has strong in-plane anisotropy. A full understanding of the anisotropy is necessary for the fabrication of future devices which may exploit these quantum and topological properties, yet a detailed study of the material’s anisotropy is currently lacking. While angle resolved Raman spectroscopy has been used to study anisotropic 2D materials, such as black phosphorus, there has been no in-depth study of the Raman dependence of 1 T´-MoTe2 on different layer numbers and excitation energies. Here, our angle resolved Raman spectroscopy shows intricate Raman anisotropy dependences of 1 T´-MoTe2 on polarization, flake thickness (from single layer to bulk), photon, and phonon energies. Using a Paczek approximation, the anisotropic Raman response can be captured in a classical framework. Quantum mechanically, first-principle calculations and group theory reveal that the anisotropic electron-photon and electron-phonon interactions are nontrivial in the observed responses. This study is a crucial step to enable potential applications of 1 T´-MoTe2 in novel electronic and optoelectronic devices where the anisotropic properties might be utilized for increased functionality and performance.